Insomnia Complaint Versus Sleep Diary Parameters: Predictions of Suicidal Ideation. Issue 1 (6th June 2015) - Woosley, Julie A.; Lichstein, Kenneth L.; Taylor, Daniel J.; Riedel, Brant W.; Bush, Andrew J.
Abstract : The purpose of this study was to determine which aspects of insomnia best predict suicidal ideation (SI). Participants were grouped according to whether they complained of insomnia and whether their sleep would be characterized as poor or good by applying quantitative criteria for insomnia to their sleep diary data. Analyses revealed that insomnia complaint was more strongly associated with SI than was poor sleep. These findings suggest that patients who complain of insomnia, regardless of the presence or absence of poor sleep, may be at greater risk for suicide than those who are content with their sleep.